Determinants of skin sympathetic nerve responses to isometric exercise - Wilson, Thad E; Dyckman, Damian J; Ray, Chester A (Journal of applied physiology (1985), 2006)
1 Division of Cardiology, Department of Medicine, and 2 Department of Cellular and Molecular Physiology, General Clinical Research Center, Pennsylvania State University College of Medicine, Hershey, Pennsylvania Submitted 17 May 2005 ; accepted in final form 27 October 2005 Exercise-induced increases in skin sympathetic nerve activity (SSNA) are similar between isometric handgrip (IHG) and leg extension (IKE) performed at 30% of maximal voluntary contraction (MVC). However, the precise effect of exercise intensity and level of fatigue on this relationship is unclear. This study tested the following hypotheses: 1 ) exercise intensity and fatigue level would not affect the magnitude of exercise-induced increase in SSNA between IHG and IKE, and 2 ) altering IHG muscle mass would also not affect the magnitude of exercise-induced increase in SSNA. In protocol 1 , SSNA (peroneal microneurography) was measured during baseline and during the initial and last 30 s of isometric exercise to volitional fatigue in 12 subjects who randomly performed IHG and IKE bouts at 15, 30, and 45% MVC. In protocol 2 , SSNA was measured in eight subjects who performed one-arm IHG at 30% MVC with the addition of IHG of the contralateral arm in 10-s intervals for 1 min. Exercise intensity significantly increased SSNA responses during the first 30 s of IHG (34 ± 13, 70 ± 11, and 92 ± 13% change from baseline) and IKE (30 ± 17, 69 ± 12, and 76 ± 13% change from baseline) for 15, 30, and 45% MVC. During the last 30 s of exercise to volitional fatigue, there were no significant differences in SSNA between exercise intensities or limb. SSNA did not significantly change between one-arm and two-arm IHG. Combined, these data indicate that exercise-induced increases in SSNA are intensity dependent in the initial portion of isometric exercise, but these differences are eliminated with the development of fatigue. Moreover, the magnitude of exercise-induced increase in SSNA responses is not dependent on either muscle mass involved or exercising limb. skin blood flow; sweat rate; microneurography Address for reprint requests and other correspondence: T. E. Wilson, Dept. of Pharmacology and Physiology, Drexel Univ. College of Medicine, 245 N. 15th St., Mail Stop 488, Philadelphia, PA 19102 (e-mail: thad.e.wilsonatdrexel.edu )